Pharmacognostic Study on Elsholtzia ciliata (Thumb.) Hyl: Anatomy, Phytochemistry and Pharmacological Activities - Qian Zhang; Niara Moura Porto; Carolina Carvalho Guilhon; Thais Biondino Sardella Giorno; Daniela Sales Alviano; Maria de Fatima Agra; Patricia Dias Fernandes; Fabio Boylan (MDPI AG, 2021)
Elsholtzia ciliata (Thunb.) Hyl, family Lamiaceae, is an important and popular anti-bacterial and anti-inflammatory Traditional Chinese Medicine (TCM). However, there are limited scientific studies on its anatomy and pharmacological activities. Moreover, the information of chemical constituents in relation to its non-volatile constituents are still missing. The current study aimed to evaluate the anatomic, pharmacological and phytochemical profile of Elsholtzia ciliata, providing means for the quality control of this herbal drug. The methodology designed for this study included the preparation of anatomic sections and their description, extraction, chromatography, structural elucidation of isolated compounds by NMR techniques and their quantification by HPLC using pharmacological assays (Formalin, hot plate, DPPH, antimicrobial-Gram positive, Gram Negative and fungus, and MTT assays) to confirm the activities described for this species. Results of the anatomic study are aligned with the pattern expected for plants belonging to the Lamiaceae family; Ursolic acid and Oroxylin were isolated from this plant species. The findings observed in this study indicate that Elsholtzia ciliata possess anti-inflammatory, antinociceptive, antioxidant, antimicrobial and anticancer activities. The chemical compounds isolated from its leaves and the anatomy profile of its parts provide the basis for further quality control for this plant.